Electrochemical measurement of intrinsic oxygen reduction reaction activity at high current densities as a function of particle size for Pt4–xCox/C (x = 0, 1, 3) catalysts - Zalitis,C; Kucernak,A; Lin,X; Sharman,J (ACS Catalysis, 2020)
While extensive literature shows Pt alloy catalysts are a more active substitute for pure Pt catalysts at 0.9 V, high activity is also needed at high current densities if they are to be adopted for fuel cell application. We use a newly developed electrochemical technique to compare the performance of a range of catalysts with initial composition Pt4–xCox/C of different particle sizes at high current densities (∼0.65 V vs RHE) as well as the typical ∼0.9 V vs RHE. Moving from 0.9 to 0.65 V, the current densities were found to increase by up to 80-fold for the Pt/C catalysts, with this factor decreasing as the amount of Co in the PtCo alloy increases. A kinetic model incorporating site blocking species at both high and low potentials has been used to explain this change. While the dealloyed catalysts were found to have a greater mass activity at low current densities (∼0.9 V vs RHE), they were no longer as active as 2.1 nm Pt particle catalyst at high current densities (∼0.65 V vs RHE). However, for equivalent particle sizes, the mass activity of the dealloyed Co-containing catalysts remains higher across the normal operating potentials of a fuel cell. Using this insight, we predict that at 0.65 V a catalyst composed of 3.8 nm CoPt@Pt1ML particles would give optimum mass activity performance. In addition, two peaks were observed during the cyclic voltammetry (CV) of the oxygen reduction reaction (ORR) on pure Pt nanoparticles in the hydrogen adsorption region (0–0.4 V vs RHE). These peaks are associated with surface sites with different reactivities toward the ORR.